SEJARAH PERKEBUNAN KELAPA SAWIT PTPN V KEBUN TANDUN DI DESA TALANG DANTO KECAMATAN TAPUNG HULU KABUPATEN KAMPAR (1996-2012 - Dewi, Intan Kumala Dewi Kumala; Melay, Ridwan Melay; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine ( 1 ) the history of oil palm plantations in PTPN V Talang Danto District of Tapung HuluKampar ( 2 ) the development of oil palm PTPN V in Talang Danto Kampar District of TapungHulu 1996-2012 ( 3 ) the impact of oil palm plantations PTPN V to the socio-economic life of the people in the village of Talang Danto District of TapungHulu Kampar . This study uses history ( History ) with data collection techniques such as observation and interviews . Speakers who used the local community , employees who are still working in PTPN V and retired employees and supported by the book - a book that deals with the study .The results showed that the background of the establishment of PTPN V is based on the Indonesian Government Regulation No. 10 In 1996 , since March 11, 1996 the company together with PT . Plantation II , PT . Plantation IV and PT . Plantation V into PT . Nusantara Plantation V. The development of oil palm plantations in PTPN V Talang Danto can be seen from several fields , such as production , labor , facilities and infrastructure that has developed from year to year . The development of oil palm plantations to give effect to the welfare of employees and the community at TalangDanto District of Tapung HuluKampar .Keywords: History of Plantation , Palm Oil , PTPN V